The Contribution of Waqf in Overcoming Agrarian Problems: A Study of Hadith - Slamet Akhmadi (International Journal of Social Science and Religion (IJSSR), 2022)
Waqf is one of the elements in Islamic teachings, as well as an instrument in Islamic economics. Hadiths that talk about waqf in particular are rarely found in the main book of hadith, but uniquely there are many hadith editors who have a meaning with waqf narrated by hadith narrators. The method in writing this article uses Takhrijul Hadith, while the approach uses descriptive qualitative. The results obtained are that there is a hadith narrator named Nafi’. This Nafi' narrated the hadith about waqf in two different sanad. After examining these two different sanad, they concluded that the quality of the sanad is Sahih. Besides that, that the use of waqf now is not only for mosques, prayer rooms, madrasas, Islamic boarding schools, cemeteries, but waqf can also contribute to agrarian matters.